PERSONALITY AMONG COLLEGE STUDENTS WITH SPECIAL REFERENCE TO URBAN AND RURAL AREA - Jadav, Sunilkumar S (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Main Purpose of the research is to measure the Personality among college students so investigator selected two groups one is urban areas college students and other is rural areas college students, both groups have 200 students. In each group has 100 urban areas college students and other one groups has 100 rural areas college students. Data were collected from Banaskantha district. Scale was use for data collection is personal datasheet and personality scale developed by Y. Singh and H. M. Singh, (2011), 2x2 factorial design was used and data were analysis by ANOVA test. Result show, Area had significant impact on the Personality of college students, the personality of urban areas students is better than the rural areas students. Sex had significant impact on the Personality of college students, the personality of females is better than the males. The interaction between area and sex had no impact on the Personality of college students.